Some Remarks on the Effectiveness of Primary Education Interventions - Olmo Silva (Institute for the Study of Labor (IZA), 2009)
In this paper I survey the recent economics of education literature in order to identify which education policies can effectively improve the quality of primary schooling, as measured by pupil test-based achievements. Particular attention is devoted to the experience of England, a country which has made substantial investments over the past decade aimed at improving its primary education. Evidence suggests that broadly scoped resource-based programmes deliver less than more targeted policies. Additionally, a growing body of research shows that interventions that enhance choice and competition among education-service providers, and motivate teachers through pecuniary rewards, have some scope in raising education standards. I conclude my survey by discussing some broad concerns with modes of education provision centred on choice and competition, mainly pupil segregation along the lines of ability and family background.
Keywords: I20; I28; H52; J24; 330; primary schools; resources; choice and competition; incentives; Bildungspolitik; Wirkungsanalyse; Bildungsökonomik; Bildungsniveau; Welt; England